Mechanical properties of high niobium TiAl alloys doped with Mo and C. (5th June 2016) - Chlupová, A.; Heczko, M.; Obrtlík, K.; Polák, J.; Roupcová, P.; Beran, P.; Kruml, T.
Abstract: Effects of alloying elements (i.e., variable content of Mo and C) on the microstructure and mechanical properties of five types of experimental material based on TiAl alloy containing 7 at.% Nb were investigated. Mechanical properties (tensile, compression and fatigue) at room and at elevated temperatures were evaluated. Addition of Mo and/or C resulted in different phase compositions and three typical microstructures. To judge the effect of alloying on the microstructure the comparison with reference TiAl alloy with 7 at.% Nb without C and Mo addition was used. Evaluation of mechanical properties of individual alloys revealed two most promising variants: (i) alloy with 2 at.% Mo containing β phase, having mixed microstructure and exhibiting the highest ductility, (ii) alloy with 0.5 at.% C having nearly lamellar microstructure, enhanced amount of α2 phase, without β phase and exhibiting the highest strength. No positive effect of combined Mo and C addition on mechanical properties was identified. Fractographic observations revealed that the major fracture mode in all alloys was trans -lamellar. Inter-lamellar fracture was observed occasionally and mainly in C containing alloys. Graphical abstract: Translamellar cleavage found as main fracture micromechanism at room temperature coupled with intergranular fracture at elevated temperatures. Highlights: Positive effects of either C or Mo on microstructure and mechanical properties of high Nb TiAl alloys are described. Combining of C and Mo does not result in improved mechanical properties. The major fatigue fracture mode in all studied materials is described as translamellar.